(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
Rich and well preserved palynological assemblages recovered from two outcrop sections in the Monte Soro Flysch (Nebrodi Mountains, NE Sicily, Italy) are documented and discussed. They provide new and valuable information for age determination and correlation within this turbidite unit in the type-area. The dinoflagellate cyst zonation scheme established for the Lower Cretaceous in the western Mediterranean region, is successfully applied to the lower portion of the Monte Soro Flysch sampled at Vallone Rosmarino, ranging in age from the latest Valanginian to the Late Hauterivian. The Pizzo Gilormo section exhibits a fining and thinning-upward sequence and is dated as Early Aptian through latest Aptian. Turbidites of the Monte dell’Abate succession are proved to be a lateral equivalent of the Monte Soro Flysch at the Pizzo Gilormo section. Overlying these turbidites, the shales cropping out at Portella Buffali mark in the Early Albian the beginning of the deposition of the Argille Scagliose Superiori. Although the Barremian was not detected in the material of the present study, it is documented both in the literature and in the succession drilled by Agip close to Randazzo. Finally, an age extending from the latest Valanginian to the latest Aptian is established by means of palynomorphs for the Monte Soro Flysch. Owing to their abundance, diversity, excellent preservation and consistent record throughout the composite succession of the Monte Soro Flysch, dinoflagellate cysts represent an optimal tool for age and palaeoenvironmental assessment within this unit. The reappraisal of the dinoflagellate species Hystrichosphaeridium? atlasiense Below is proposed: a single-plate precingular archeopyle is documented for the cyst, which precludes its assignment to the genus Hystrichosphaeridium Deflandre and suggests the attribution to the genus Kleithriasphaeridium Davey, herein emended. The first appearance of Kleithriasphaeridium atlasiense (Below, 1982) Torricelli comb. nov. is proposed as an important biostratigraphic event close to the Aptian/Albian boundary in the Tethyan Realm.